Pengaruh Variasi Suhu Awal Reagen terhadap Kadar Glukosa Darah Metode Enzimatik - Yayuk Kustiningsih; Nastiti Megawati; Jasmadi Joko Kartiko; Leka Lutpiatina (Medical Laboratory Technology Journal, 2017)
Pre-analysis phase is the first step that determines the quality of the examination results, in this case, is the preparation of glucose work reagent. Glucose is one of the clinical examination clinical parameters that are often done in the laboratory. This glucose examination uses enzymatic methods. Enzyme activity is influenced by several factors, namely temperature, pH, substrate level, enzyme level, and inhibitor. Glucose examination performed at a temperature of 20-25oC or 37oC, but there are still laboratories in the field that is less attention to the initial temperature conditions of this reagent. This study aims to determine the effect of initial temperature variations of reagents on blood glucose levels of enzymatic methods. The research used Quasi Experimental research method with Posttest-Only Control Group Design design. The sample of this research used serum of a respondent who had no history of Diabetes Mellitus disease with 4 replication at each treatment. The results of the study with the initial temperature of 10oC, 13oC, 16oC, 19oC, 22oC and 25oC (control) respectively of 62.71 mg / dL; 65,74 mg / dL; 72.45 mg / dL; 76.91 mg / dL; 89.12 mg / dL and 97.19 mg / dL, the results of this study showed an increase in glucose levels in each treatment. Based on the results of linear regression analysis obtained a significance value of 0.000 with α = 0.05, which means Ho is rejected, so it can be concluded that there is an influence of initial temperature variation of reagent on blood glucose level. For the next researcher can do research about the effect of the initial temperature of reagent 22-38 oC on blood glucose enzymatic method. And the influence of incubation time on blood glucose level of enzymatic method.